2018
DOI: 10.1186/s12931-018-0931-8
|View full text |Cite
|
Sign up to set email alerts
|

Roles of mitochondrial ROS and NLRP3 inflammasome in multiple ozone-induced lung inflammation and emphysema

Abstract: BackgroundMitochondrial damage leading to oxidant stress may play an important role in the pathogenesis of airflow obstruction and emphysema. NLPR3 inflammasome can be activated by mitochondrial ROS (mtROS) and other stimuli. We examined the importance of mtROS and NLRP3 inflammasome and their interactions in multiple ozone-induced lung inflammation and emphysema.MethodsC57/BL6 mice were exposed to ozone (2.5 ppm, 3 h) or filtered air twice a week over 6 weeks. MitoTEMPO (20 mg/kg), an inhibitor of mtROS, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 38 publications
1
55
0
Order By: Relevance
“…VX765 is a potent, selective caspase-1 inhibitor that inhibits the expressions of pyroptosis-associated inflammasomes and IL-1β as well as IL-18 production and attenuates pyroptosis in vitro [33,34]. Previous researches have shown that VX765 inhibits the expressions as well as the activities of NLRP3 and caspase-1 pathways in the lung [35]. Others have reported that VX765 can prevent bone erosion and reduce serum cytokine levels in arthritis [70].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VX765 is a potent, selective caspase-1 inhibitor that inhibits the expressions of pyroptosis-associated inflammasomes and IL-1β as well as IL-18 production and attenuates pyroptosis in vitro [33,34]. Previous researches have shown that VX765 inhibits the expressions as well as the activities of NLRP3 and caspase-1 pathways in the lung [35]. Others have reported that VX765 can prevent bone erosion and reduce serum cytokine levels in arthritis [70].…”
Section: Discussionmentioning
confidence: 99%
“…Mice were isolated and reared for 1 week and then randomized into four groups: sham surgery, controlled cortical impact (CCI), CCI+vehicle (DMSO), and CCI+VX765. VX765 (catalog number: HY-13205; MedChemExpress, Monmouth Junction, NJ, USA) dissolved in DMSO was injected intraperitoneally (100 mg/kg) 1 h after CCI and every 2 days after CCI for two weeks [33,35]. At the same time point, the CCI+vehicle group was given an equal volume of DMSO.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It inhibits collagen-induced arthritis and lung inflammation in mouse models. 130,131 It partly decreases bone resorption in the periapical lesion of rat experimental apical periodontitis. 80 In addition to its anti-inflammatory effect, VX-765 also has a protective role against cell death.…”
Section: Inflammasome Inhibitorsmentioning
confidence: 99%
“…NLRs form multisubunit protein complexes termed inflammasomes that activate caspase-1 resulting in proteolytic cleavage and pro-inflammatory cytokine IL-1β maturation [153,154]. Pathogenassociated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs) such as lipopolysaccharide (LPS), asbestos, ATP and uric acid activate NLR family pyrin domain containing 3 (NLRP3) inflammasome via mROS generation [155,156]. Pharmacologic or genetic inhibition of autophagy elevates mROS concentration, which heightens inflammasome activation [157,158].…”
Section: Immunitymentioning
confidence: 99%